EFFECT OF PRICE, QUALITY PRODUCTS AND BRAND IMAGE PURCHASE DECISIONS GETUK PISANG "SARI MADU" KEDIRI - Prasastono, Ndaru; Rahmawati, Ema; Fajar Pradapa, Sri Yulianto (Proceeding SENDI_U, 2017)
This study was conducted to examine and analyze the effect of price, product quality and brand image on purchasing decisions getuk pisang "Sari Madu" Kediri, either partially or simultaneously. The method used in this research is explanatory method, by taking a sample of 100 consumers, data collection techniques such as observation, questionnaires, and literature.The results of data analysis showed that the price of partial influence on purchase decisions with standardized beta coefficient of 0.781, or 78.1%, product quality influence on purchase decisions with standardized beta coefficient of 0.892 or 89.2%, while the brand image influence on purchase decisions with standardized beta coefficient of 0.950 or 95.0%. While simultaneously indicated by the coefficient of determination adjusted R Square of 0.978, which means that the variable price, product quality and brand image are able to explain 97.8% change in purchasing decisions getuk pisang "Sari Madu" Kediri, the remaining 2.2% is influenced by other factors out of the study.While the most dominant influence on purchase decisions getuk pisang "Sari Madu" Kediri is the price variable is the standardized beta coefficient of 0.766 or 76.6%. Keywords: Price, Quality Product, Brand Image, Purchase Decision